2016
DOI: 10.1111/mice.12228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Road Surface, Vehicle, and Device Characteristics on Energy Harvesting from Bridge–Vehicle Interactions

Abstract: Energy harvesting to power sensors for structural health monitoring (SHM) has received huge attention worldwide. A number of practical aspects affecting energy harvesting and the possibility of health monitoring directly from energy harvesters is investigated here. The key idea is the amount of power received from a damaged and an undamaged structure varying and the signature of such variation can be used for SHM. For this study, a damaged bridge and an undamaged bridge are considered with harvesters located a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Initial research on such an approach has been shown to be an effective in investigating applications of cantilever based piezoelectric EHDs with seismic sources (Elvin at al. 2006) and a bridge application under operational conditions (Cahill et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Initial research on such an approach has been shown to be an effective in investigating applications of cantilever based piezoelectric EHDs with seismic sources (Elvin at al. 2006) and a bridge application under operational conditions (Cahill et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The data provided here is related to deployment and monitoring of Pershagen Bridge, Sweden using piezoelectric energy harvesters [1] and is related to earlier studies on the concept of vibration energy harvesting based monitoring of built infrastructure [2] , [3] , [4] . A total of six energy harvesting devices with different natural frequencies designed around the natural frequency of the bridge are deployed and the bridge is tested using a shaker with swept sinusoidal loading with different frequency ranges and for different magnitudes of loads.…”
Section: Datamentioning
confidence: 99%
“…To study the vibration attenuation performance of the VAT at low frequencies, a three‐dimensional coupled dynamic model of a metro vehicle‐VAT‐subgrade system is established, as shown in Figure . This model is developed based on the vehicle‐track coupled dynamics theory (Zhai et al., ) which has been applied as a fundamental method to study train and track interaction issues, covering structural health monitoring (Cahill et al., ), train running behavior (Ling et al., ), defective track‐induced vibrations (Grossoni et al., ; Zhu et al., ), and vibration control of track structures (Zhu et al., ).…”
Section: Dynamic Modeling and Analysis Of The Vat Performance Under Vmentioning
confidence: 99%